2020
DOI: 10.1002/arch.21755
|View full text |Cite
|
Sign up to set email alerts
|

Two calcium‐binding chaperones from the fat body of the Colorado potato beetle, Leptinotarsa decemlineata (Coleoptera: Chrysomelidae) involved in diapause

Abstract: Molecular chaperones are crucial for the correct folding of newly synthesized polypeptides, in particular, under stress conditions. Various studies have revealed the involvement of molecular chaperones, such as heat shock proteins, in diapause maintenance and starvation; however, the role of other chaperones in diapause and starvation relatively is unknown. In the current study, we identified two lectintype chaperones with calcium affinity, a calreticulin (LdCrT) and a calnexin (LdCnX), that were present in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…In drosophilids, suppressing the expression of Hsp23 andHsp70 by RNAi did not alter the commitment to enter diapause or the duration of diapause, but it is critical for cold survival during diapause in insects ( Rinehart et al, 2007 ). Furthermore, the adipose body-specific expression of two calcium-binding chaperones (LDCRT and LDCNX) in L. decemlineata during diapause revealed the same expression pattern in relation to diapause; there was no alteration in females and downregulation in males post-diapause ( Doğan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
“…In drosophilids, suppressing the expression of Hsp23 andHsp70 by RNAi did not alter the commitment to enter diapause or the duration of diapause, but it is critical for cold survival during diapause in insects ( Rinehart et al, 2007 ). Furthermore, the adipose body-specific expression of two calcium-binding chaperones (LDCRT and LDCNX) in L. decemlineata during diapause revealed the same expression pattern in relation to diapause; there was no alteration in females and downregulation in males post-diapause ( Doğan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 92%
“…Specifically, the decreases were around 14 and 12% in third and fifth instar larvae, respectively. Various studies in mammals and insects revealed the involvement of dietary Ca 2+ and specific Ca 2+ signaling genes in lipid metabolism, leading to lipolysis ( Allen and Beck, 1986 ; Shi et al, 2001 ; Zemel, 2002 ; Jacqmain et al, 2003 ; Arruda and Hotamisligil, 2015 ; Maus et al, 2017 ; Doğan et al, 2021a , b ; Toprak et al, 2021 ). In Drosophila, elevated cytosolic Ca 2+ levels lead to activation of lipolysis ( Subramanian et al, 2013a , b ; Baumbach et al, 2014a , b ; Bi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…HFD, HSD, a calcium-rich diet (CRD), and a plant-based diet (PBD) were supplied throughout the larval development and compared to a standard artificial bean diet. The CRD was included as studies have indicated the involvement of Ca 2+ signaling molecules, cellular, and dietary Ca 2+ in lipid and carbohydrate metabolism, body weight regulation, obesity, and diabetes in insects and mammals ( Zemel et al, 2000 ; Shi et al, 2001 ; Zemel, 2002 ; Jacqmain et al, 2003 ; Baumbach et al, 2014a , b ; Arruda and Hotamisligil, 2015 ; Maus et al, 2017 ; Alomaim et al, 2019 ; Doğan et al, 2021a , b ; Toprak et al, 2021 ). The PBD (lettuce leaves) was used as lettuce is a natural host for S .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on finding alleles linked with resistance 18,19 and gene expression linked with resistance 20 . The CPB has also been used as a model to understand insect development and physiology [21][22][23] , insect diapause [24][25][26][27] , and more recently insect lipid metabolism and calcium signaling 28,29 as well as behavior 30 .…”
Section: Background and Summarymentioning
confidence: 99%